Edukasi Dan Pelatihan Budidaya Toga Di Pekarangan Rumah Warga Di Desa Pakuli - formakip formakip (Jurnal Pengabdian Masyarakat Akademisi, 2023)
Based on the results of our observations, there are problems that are of concern in Pakuli Village. One of the problems is that there are still many yards of residents' houses that are empty and not used as a place to plant family medicinal plants or "living pharmacies". The Ormawa PPK program aims to provide education and training in TOGA cultivation in the home yard. This type of research uses a pre-experimental research design with a one group pre test-post test approach using a questionnaire method. Based on the results of the educational activities that have been carried out, it can be concluded that there has been an increase in understanding and knowledge about the cultivation of TOGA plants, namely as much as 30% and various types of family medicinal plants (TOGA). each other's house.